RNF4 negatively regulates NF‐κB signaling by down‐regulating TAB2. Issue 19 (20th August 2015) - Tan, Bo; Mu, Rui; Chang, Yan; Wang, Yu-Bo; Wu, Min; Tu, Hai-Qing; Zhang, Yu-Cheng; Guo, Sai-Sai; Qin, Xuan-He; Li, Tao; Li, Wei-Hua; Zhang, Xue-Min; et al.
Abstract : Most of NF‐κB (nuclear factor kappa B) signaling molecules have various types of post‐translational modifications. In this study, we focused on ubiquitination and designed a siRNA library including most ubiquitin‐binding domains. With this library, we identified several candidate regulators of canonical NF‐κB pathway, including RNF4. Overexpression of RNF4 impaired NF‐κB activation in a dose‐dependent manner, whereas RNF4 knockdown potentiated NF‐κB activation. We showed that RNF4 interacts with the TAK1–TAB2–TAB3 complex, but not TAB1. Further, we found that RNF4 specifically down‐regulated TAB2 through a lysosomal pathway, and knockdown of RNF4 impaired endogenous TAB2 degradation. Therefore, our findings will provide new insights into the negative regulation of NF‐κB signaling. Abstract : We designed a siRNA library targeted genes correlated with ubiquitin‐binding. We screened canonical NF‐κB signaling for regulators by using the library. One of the candidates RNF4 was confirmed as a negative regulator of NF‐κB signaling. RNF4 interacted with and down‐regulated TAB2 through lysosomal pathway.